A Review of“Basics of Islamic Law Inference” Book - Sayyid Abdolrahim Hosseini (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Devotion to rules of writing educational books of humanities, especially in jurisprudence, legal issues, and principles of jurisprudence, is an inevitable requirement. According to the investigation on the manner of writing and configuration of scientific topics and contents of “Basics of Islamic Law Inference” book,  some issues such as lack of style cohesion in classifying topics, ignoring logic of complication and recent achievements, lack of logical relationship between some of the described issues, non-using required documents, impracticality of described issues, heterogeneity of reasoning, ignoring key doctrines, lack of using new legal findings and revised books made this book reviewable; on the other hand, the practical requirement for composing legal educational texts and its conformity with the latest finding and adaptation with applicable law in various areas, emphasizing the theories of jurisprudents and using their latest achievements are essential for jurisprudence texts. Since the book mentioned herein is for education which should make students feel ready for conducting legal research based on the fundamental views, it seems that it is essential to revise its topics as a source of higher education and employment examination.